Divertor detachment of high βN H-mode discharges with the HL-2A closed divertor geometry. (1st November 2022) - Gao, J M; Cai, L Z; Cao, C Z; Ma, H C; Ke, R; Zhong, W L; Wu, N; Hu, Y; Gao, X Y; Cui, C H; Huang, Z H; Nie, L; et al.
Abstract: Divertor detachment of high β N H-mode discharges has been achieved by the injection of radiating impurities in the very closed divertor geometry of HL-2A. Non-intrinsic impurity is injected into the outer divertor chamber, and enhanced volumetric energy loss in the divertor and decreased divertor heat flux are then observed. Divertor detachment leads to a little degradation of the core confinement, characterized by slight decrease of plasma stored energy and pedestal pressure as well as increase of edge localized mode (ELM) frequency, but the high β N H-mode is still sustained with β N > 2 and H98 > 1. After impurity injection, the pedestal density fluctuation is increased, implying that the enhanced pedestal transport might be responsible for the degradation. During divertor detachment phase, the impurities are well controlled in the divertor without strong radiation losses near X-point region, and the main plasma density does not increase, but decreases slightly, which could be contributed by the very closed divertor geometry. These results are encouraging to achieve better heat load control and high plasma performance simultaneously for tokamak operations and to evaluate the effect of the divertor geometry for future tokamak devices.